2020
DOI: 10.1111/cas.14640
|View full text |Cite
|
Sign up to set email alerts
|

Intranodal pressure of a metastatic lymph node reflects the response to lymphatic drug delivery system

Abstract: Cancer metastasis to lymph nodes (LNs) almost certainly contributes to distant metastasis. Elevation of LN internal pressure (intranodal pressure, INP) during tumor proliferation is associated with a poor prognosis for patients. We have previously reported that a lymphatic drug delivery system (LDDS) allows the direct delivery of anticancer drugs into the lymphatic system and is a promising treatment strategy for early‐stage LN metastasis. However, methods for evaluating the treatment effects have not been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Elevated intranodal pressure (INP) can be utilized as a diagnostic tool for early‐stage MLNs. A correlation between INP and therapeutic response has also been established by our group 23 . Additionally, previous studies have attributed pin prick leak, that is, drug leakage from pin prick due to uniformly elevated interstitial fluid pressure in solid tumors, to explain insufficient drug accumulation in the target tissue 21 .…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Elevated intranodal pressure (INP) can be utilized as a diagnostic tool for early‐stage MLNs. A correlation between INP and therapeutic response has also been established by our group 23 . Additionally, previous studies have attributed pin prick leak, that is, drug leakage from pin prick due to uniformly elevated interstitial fluid pressure in solid tumors, to explain insufficient drug accumulation in the target tissue 21 .…”
Section: Introductionsupporting
confidence: 59%
“…A correlation between INP and therapeutic response has also been established by our group. 23 Additionally, previous studies have attributed pin prick leak, that is, drug leakage from pin prick due to uniformly elevated interstitial fluid pressure in solid tumors, to explain insufficient drug accumulation in the target tissue. 21 It is likely that the same effect is exerted in the case of localized administration of chemotherapeutic agents to MLNs, that is, high intranodal pressure results in the leakage of injected drug solution out of the needle puncture, resulting in a pin prick leak.…”
Section: Introductionmentioning
confidence: 99%
“…(8) Inguinal lymph node: Usually, one on each side, 2–5 mm in size, located in the lateral abdominal fold of the groin area, close to the subcutaneous, easy to peel off and lose with the skin when separated. Due of its superficial position, it has become the main site of injection treatment called the lymphatic drug delivery system (LDDS) [ 20 ]. (9) Sciatic lymph node: It is located on the ventral side of the superficial gluteus muscle, on the side of the sciatic tuberosity, and above the sciatic nerve near the spine, one on each side, and the size is approximately 4–5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Bouta et al described intranodal popliteal and axillary pressures of an average 9 and 12 cmH2O, respectively, in normal wild type mice 14 . Kato et al and Miura et al used MXH10/Mo-lpr/lpr, a mouse model that develops systemic swelling of lymph nodes, obtaining lower values for intranodal pressures 15,16 . Miura et al showed that mean pressures within subiliac and axillary nodes were 0.10 cm H2O and 0.03 cm H2O, respectively 16 .…”
Section: Discussionmentioning
confidence: 99%